Associations between family food behaviors, maternal depression, and child weight among low-income children - McCurdy, Karen (2014)
Although low-income children are at greater risk for overweight and obesity than their higher income counterparts, the majority of poor children are not overweight. The current study examined why such variation exists among diverse young children in poor families. Cross-sectional data were collected on 164 low-income, preschool aged children and their mothers living in two Rhode Island cities. Over half of the sample was Hispanic (55%). Mothers completed measures of family food behaviors and depression while trained assistants collected anthropometric data from children at seven day care centers and a Supplemental Nutrition Assistance Program outreach project. Multivariate analysis of covariance revealed that higher maternal depression scores were associated with lower scores on maternal presence when child eats (P < .05), maternal control of child’s eating routines (P < .03), and food resource management skills (P < .01), and with higher scores on child control of snacking (P < .03) and negative mealtime practices (P < .05). Multiple regression results revealed that greater maternal presence whenever the child ate was significantly associated with lower child BMI z scores (β = .166, P < .05). Logistic regression analyses indicated that higher scores on food resource management skills reduced the odds of child overweight (odds ratios = .72 – .95, P < .01). Maternal depression did not modify the relationship between family food behaviors and child weight. Overall, caregiver presence whenever a child eats, not just at meals, and better parental food resource management skills may promote healthier weights in low-income preschoolers. Further research is needed to identify the mechanisms that connect caregiver presence and food resource management skills to healthier weights for this age group.